Impact Of Pharmacist Intervention On Clinical Outcomes, Quality Of Life, Cost Of Treatment And Complications Among Diabetic Patients In Dmtac, Kedah, Malaysia - Iqbal, Muhammad Zahid (2021)
The present study was conducted to evaluate the impact of pharmacist intervention in DMTAC clinics on clinical outcomes, quality of life, cost of treatment and complications among diabetic patients in two public hospitals of Kedah Malaysia. The current study design was randomized controlled trial and was ethically approved from the Medical Research and Ethics Committee (MREC) Malaysia.